Protective Property of Scutellarin Against Liver Injury Induced by Carbon Tetrachloride in Mice - Miao, Zhimin; Lai, Yong; Zhao, Yingying; Chen, Lingmin; Zhou, Jianeng; Li, Chunyan; Wang, Yan (Frontiers in Pharmacology, 2021)
Liver injury is a clinical disorder caused by toxins, drugs, and alcohol stimulation without effective therapeutic approaches thus far. Scutellarin (SCU), isolated from the edible herb Erigeron breviscapus (Vant.) Hand. -Mazz. showed potential hepatoprotective effects, but the mechanisms remain unknown. In this study, transcriptomics combined with nontargeted metabolomics and 16S rRNA amplicon sequencing were performed to elucidate the functional mechanisms of SCU in carbon tetrachloride (CCl4)–induced liver injury in mice. The results showed that SCU exerted potential hepatoprotective effects against CCl4-induced liver injury by repressing CYP2E1 and IκBα/NF-κB signaling pathways, modulating the gut microbiota (especially enriching Lactobacillus), and regulating the endogenous metabolites involved in lipid metabolism and bile acid homeostasis. SCU originates from a functional food that appears to be a promising agent to guard against liver injury.